PENGARUH KEPEMIMPINAN, DISIPLIN, DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PT. BHUMI PHALA PERKASA BALIKPAPAN - Ana Mika, Yestari; Juwari, Juwari (MEDIA RISET EKONOMI [MR.EKO], 2025)
This research aims to determine the influence of leadership, discipline and work environment on the work spirit of Balikpapan University educational staff. The population in this research was 62 Balikpapan University education staff. By using a census or total sampling with a total population of 62 Balikpapan University education staff. The data collection method was carried out by distributing questionnaires. This research uses SmartPLS to process data. The results of this research indicate that the leadership variable has a positive and insignificant effect on the work spirit of the Balikpapan University educational staff. The discipline variable has a positive and significant effect on the morale of the Balikpapan University educational staff. Work environment variables have a positive and significant effect on the work spirit of Balikpapan University educational staff.